Analisis Rasio Keuangan Daerah dalam Menilai Kinerja Keuangan Pemerintah Kabupaten Solok Selatan, Kabupaten Tanah Datar, dan Kabupaten Agam Tahun 2023–2024 - Elvina Indriati; Winda Yanti; Nurlisafani Nurlisafani; Etsa Fahimah; Siska Yulia Defitri; Rita Dwi Putri (Jurnal Ilmu Sosial dan Humaniora, 2026)
This study aims to analyze and compare the financial performance of the South Solok Regency, Tanah Datar Regency, and Agam Regency for the 2023–2024 fiscal year using local government financial ratio analysis. This study employs a descriptive quantitative method, utilizing secondary data in the form of Budget Implementation Reports (LRA) obtained through documentation from the official websites of each local government. The analysis was conducted using autonomy ratios, effectiveness ratios, efficiency ratios, and balance ratios—which include operating expenditure ratios and capital expenditure ratios—revenue growth ratios, and fiscal decentralization ratios. The results indicate that all three regencies still exhibit low levels of financial autonomy and fiscal decentralization, leaving them dependent on central government transfer funds. Tanah Datar Regency has the highest level of local revenue (PAD) effectiveness, while South Solok Regency and Agam Regency demonstrate better efficiency in financial management. Furthermore, the proportion of operating expenditures remains higher than that of capital expenditures, even though all regencies showed positive revenue growth in 2024. Thus, local governments need to optimize local revenue, improve budget management efficiency, and balance expenditure allocations to achieve sustainable fiscal autonomy.